Antibacterial activity and mechanism of Sodium houttuyfonate against heteroresistant Pseudomonas aeruginosa - Li, Zhihong; Zhang, Tongtong; Wang, Ziqi; Huang, Shuqiang; Tan, Cuiyu; Wang, Dan; Yuan, Xiaojun; Xu, Lingqing (Frontiers in Microbiology, 2025)
BackgroundPseudomonas aeruginosa is a common gram-negative opportunistic pathogen that is now commonly treated with carbapenems, such as Meropenem. However, the increasing rate of emergence of heteroresistant strains poses a therapeutic challenge. Therefore, we examined the antibacterial activity of Sodium houttuyfonate (SH, a compound derived from Houttuynia cordata) in combination with Meropenem (MEM) against heteroresistant Pseudomonas aeruginosa and investigated the mechanism of Sodium houttuyfonate.MethodsHeteroresistant Pseudomonas aeruginosa was used as the experimental strain for the study and the combined action activity of the two drugs was inves-tigated by determining the Minimum Inhibitory Concentration (MIC), Fractional Inhibitory Concentration Index (FICI), and time killing curves. Also the effect of Sodium houttuyfonate on biofilm as well as bacterial swimming motility assay was investigated by crystal violet staining of bacterial biofilm, microanalysis of biofilm, bacterial swimming motility assay, quantitative real-time PCR (qRT-PCR) and population sensing related virulence factors.ResultsFor the screened experimental strains, the MIC of SH was 4,000 μg/ml; the FICI of both drugs on the four experimental strains was ≤0.5, which showed a synergistic effect. When SH ≥ 250 μg/ml, it was able to effectively inhibit bacterial biofilm formation as well as swimming ability compared with the blank control group. In the qRT-PCR experiment, the expression of biofilm formation-related genes (pslA, pelA, aglD, lasI, lasR, and rhlA) and swimming ability-related genes (fliC, pilZ, and pilA) were decreased in the SH-treated group, compared with the blank control group.ConclusionOur study demonstrated that Sodium houttuyfonate and Meropenem exhibited synergistic inhibition against heteroresistant Pseudomonas aeruginosa, and that Sodium houttuyfonate may achieve its inhibitory effect by inhibiting bacterial biofilm formation, inhibiting motility, and down-regulating related genes.